2015
DOI: 10.1016/j.physbeh.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of menstrual cycle phase and sexual activity predicts mucosal and systemic humoral immunity in healthy women

Abstract: Several studies have documented shifts in humoral immune parameters (e.g., immunoglobulins) across the menstrual cycle in healthy women. It is thought that these shifts may reflect dynamic balancing between reproduction and pathogen defense, as certain aspects of humoral immunity may disrupt conception and may be temporarily downregulated at ovulation. If so, one could expect maximal cycle-related shifts of humoral immunity in individuals invested in reproduction – that is, women who are currently sexually act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
(65 reference statements)
0
15
0
1
Order By: Relevance
“…The higher the frequency of intercourse, the greater the mid-cycle decline in pro-inflammatory markers (and mid-cycle increase in anti-inflammatory markers). Prior research in healthy women has shown that sexual activity is associated with lower levels of IgA (16, 19), IgE-mediated allergic responses (57), and Th1-dominant cytokine profiles (20). One common theme throughout these seemingly diverse immune factors is their potential detrimental effect on reproduction, via disruption of conception (as IgA may disrupt sperm transport and viability (58)), interference with establishment of the placenta (as when IgE is diverted from supporting the placenta towards allergic reactions(59)), or through early termination of the pregnancy (as is the case for Th1 cells(60) particularly in the context of low Th2 cells(61)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the frequency of intercourse, the greater the mid-cycle decline in pro-inflammatory markers (and mid-cycle increase in anti-inflammatory markers). Prior research in healthy women has shown that sexual activity is associated with lower levels of IgA (16, 19), IgE-mediated allergic responses (57), and Th1-dominant cytokine profiles (20). One common theme throughout these seemingly diverse immune factors is their potential detrimental effect on reproduction, via disruption of conception (as IgA may disrupt sperm transport and viability (58)), interference with establishment of the placenta (as when IgE is diverted from supporting the placenta towards allergic reactions(59)), or through early termination of the pregnancy (as is the case for Th1 cells(60) particularly in the context of low Th2 cells(61)).…”
Section: Discussionmentioning
confidence: 99%
“…If so, it would follow that these effects would be most critical (and most subject to evolutionary selective pressure) in individuals who are reproductively active, i.e., regularly engaging in sexual activity. Indeed, several studies suggest that immune parameters, including inflammatory cytokines, differ in sexually active vs. abstinent women (1618), with sexually active women showing more variation in immune markers across the menstrual cycle than abstinent women (13, 19, 20). Thus, we would expect that inflammation would differ significantly across the menstrual cycle in sexually active, but not abstinent, women.…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis was drawn from a larger study on the effects of sexual activity on women’s health; other papers from this study include (Lorenz et al, 2015a; Lorenz et al, 2015b). …”
Section: Methodsmentioning
confidence: 99%
“…One study of healthy participants found no association between endogenous T and SIgA in either men or women (van Anders, 2010); however, this study did not report the menstrual phase of the female participants. IgA has been found to be significantly different across cycle phases (Gomez et al, 1993; Lorenz et al, 2015a), although other studies have found no significant cycle-related variation (Brown et al, 2008; Garde et al, 2000; Gillum et al, 2014). …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation